Implementation of Productive Zakat and Cash Waqf for Micro- Entrepreneurs: A Legal and Regulatory Review - Aen Fariah (Journal of Social Research, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continue to face structural challenges, especially in accessing financing and empowerment, particularly at the micro level. This study aims to analyze the implementation of productive zakat and cash waqf by the Zakat Collection Unit (UPZ) of STAI Kuningan in supporting micro-entrepreneurs, and to evaluate its compliance with Islamic law and national regulations. This qualitative research uses a juridical-normative and juridical-empirical approach. Data were obtained through interviews, documentation, and literature review, then analyzed descriptively and qualitatively. The findings show that the program has effectively empowered micro-enterprises through business capital, equipment support, and mentoring. Normatively, the practice complies with the objectives of sharia (maqashid syariah), the fatwas of the Indonesian Ulema Council (MUI), and Indonesian laws on zakat and waqf. Nevertheless, institutional and regulatory barriers remain, including the absence of technical guidelines and limited coordination with national zakat authorities. Strengthening legal frameworks and operational procedures is recommended to enhance the institutional role of campus-based UPZ in advancing community-based Islamic economics.